Dual conical shell illumination for volumetric high-energy X-ray diffraction imaging. Issue 20 (19th September 2018) - Dicken, Anthony; Spence, Daniel; Rogers, Keith; Prokopiou, Danae; Evans, Paul
Abstract : To retrieve crystallographic information from extended sample volumes requires a high-energy probe. Abstract : To retrieve crystallographic information from extended sample volumes requires a high-energy probe. The use of X-rays to combine imaging with materials characterisation is well-established. However, if fundamental crystallographic parameters are required, then the collection and analysis of X-rays diffracted by the inspected samples are prerequisites. We present a new X-ray diffraction imaging architecture, which in comparison with previous depth-resolving hollow beam techniques requires significantly less X-ray power or alternatively supports significantly increased scanning speeds. Our conceptual configuration employs a pair of conical shell X-ray beams derived from a single point source to illuminate extended samples. Diffracted flux measurements would then be obtained using a pair of energy resolving point detectors. This dual beam configuration is tested using a single X-ray beam set-up employing a dual scan. The use of commercial off-the-shelf low-cost components has the potential to provide rapid and cost-effective performance in areas including industrial process control, medical imaging and explosives detection.